Higher education institutions' impact on the economy - Agnė Vaiciukevičiūtė; Jelena Stankevičienė; Nomeda Bratčikovienė (Journal of Business Economics and Management (JBEM), 2019)
Despite the strong public interest in the accountability and efficiency in education spending on higher education institutions (HEIs) in Lithuania, there are currently no existing studies which have examined the impact of HEIs on the country's economy. In the present study, we have used a disaggregated input-output table for Lithuania's tertiary education institutions in order to determine the output value added to the local economy by the presence of HEIs. The results of the study have revealed that HEIs contribute to the Lithuanian economy in the period of (2010-2016), with the average of gross domestic output (GDP) of 298.48 mln. euros. The present study is the first of its kind to use input-output table evaluate the impact of HEIs on Lithuania's economy, and its results could be of significant value to the current policy debates regarding the status of higher education in Lithuania.
Keywords: G32; O32; O34; 650; Higher education institutions (HEIs); economic impact; input-output analysis; universities; Lithuania